South Pacific Agricultural News, January 2008 - Samasoni, Aterina; Umar, Mohammed (IRETA/CTA, 2008)
Themes covered in this issue include: new technology for improved coffee, taro market in Samoa, peanut research and .. Samoa’s organic coconut oil for cosmetic products.